Sanibel Flats - White, Randy Wayne (White, Randy Wayne. Doc Ford series., 1991)
There's a murder committed on a deserted mangrove island on Florida's west coast. Doc Ford must return to mountain camps of armed guerillas in Central America to save a friend's young boy.